2001
DOI: 10.1046/j.1365-2044.2001.02105.x
|View full text |Cite
|
Sign up to set email alerts
|

Hypertension as a risk factor for cerebral injury during cardiopulmonary bypass

Abstract: SummaryWe studied 22 patients aged 53±78 years scheduled for cardiac surgery under cardiopulmonary bypass. Blood pressure, cardiac output, transcranial Doppler blood flow velocity, arterial blood gases, body temperature and protein S100B, as a marker for cerebral integrity, were evaluated in normotensive and hypertensive patients. Pre-operative mean (SD) arterial blood pressure was 93 (11) mmHg in the normotensive group compared with 116 (15) mmHg in the hypertensive group. We found an increase in protein S100… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 24 publications
0
16
0
Order By: Relevance
“…40 A small cohort study of 22 patients then suggested that preoperative chronic hypertension is associated with higher levels of S100B in cardiac surgery patients. 41 The authors speculated that the poor cerebral blood flow autoregulation secondary to chronic hypertension might predispose BBB dysfunction during CPB and thus initiate the release of S100B. 41 There was a positive correlation between postoperative serum levels of S100B and age in 56 patients who underwent coronary artery bypass graft (CABG) surgery.…”
Section: S100b In Cardiac Surgerymentioning
confidence: 99%
“…40 A small cohort study of 22 patients then suggested that preoperative chronic hypertension is associated with higher levels of S100B in cardiac surgery patients. 41 The authors speculated that the poor cerebral blood flow autoregulation secondary to chronic hypertension might predispose BBB dysfunction during CPB and thus initiate the release of S100B. 41 There was a positive correlation between postoperative serum levels of S100B and age in 56 patients who underwent coronary artery bypass graft (CABG) surgery.…”
Section: S100b In Cardiac Surgerymentioning
confidence: 99%
“…However, in these studies the investigators did not separately analyze patients with hypertension who, as a result of altered cerebrovascular autoregulation, might be at greater risk for decreased cerebral perfusion secondary to decreased systemic blood pressure 7. This view is supported by a study of patients undergoing cardiac surgery, which demonstrated that hypertensive patients had higher postoperative increases in peripheral blood levels of S100B, a marker of cerebral injury 8. They hypothesized that this larger increase was the result of altered cerebrovascular autoregulation, and suggested that cardiopulmonary bypass management protocols may need adjustment to improve cerebral perfusion in hypertensive patients.…”
mentioning
confidence: 99%
“…Our findings suggest that BIS sensors should be placed on the non‐diseased side of the forehead in patients with unilateral carotid artery or cerebrovascular disease. In addition, hypertensive patients with carotid artery disease may be more susceptible to low arterial blood pressure due to the shifting upwards of the cerebral autoregulation curve 7,8 and impaired cerebral autoregulation distal to carotid stenosis 9 . Therefore, during operation in these patients, blood pressure increase may be needed to increase cerebral blood flow and subsequent oxygen supply in brain regions with impaired autoregulation.…”
Section: Discussionmentioning
confidence: 99%